Contemporary artist/teacher meets a mid-century classroom: Practice, theory and becoming an art teacher. Issue 1 (1st March 2019) - Graham, Mark Allen; Estrada, Tara Carpenter
Student teaching is one of the most important and demanding parts of teacher preparation. Student teachers balance many concerns, including classroom management, apathetic students, the demands and expectations of a full-time teacher, how to dress, how to get along with their mentor teacher, and how to meet the expectations of the licensure process that typically includes complex assessments of their teaching practices. These case studies illustrate how student teachers may also need to navigate philosophical differences with their mentoring teacher about art, education and classroom management. These differences also create distinct portraits of conflicts in art education between emerging and traditional pedagogical practices. Creating a productive collaboration between university and school and between the student teachers and their mentors is a challenge that requires careful attention to the existing culture and teaching practices of the mentoring teacher and the emerging methods of the student teacher.